Engaging individual learning through collaborative knowledge building processes: a hybrid framework. (1st January 2014) - Collins, Regina; Deek, Fadi P.
The globalisation of engineering teams has increasingly demanded technologies that support collaboration and knowledge sharing while also respecting the cultural and cognitive differences of individual team members. Existing collaborative knowledge building systems apply a one-size-fits-all approach to knowledge building, allowing individuals to contribute to collective knowledge but overlooking individual knowledge backgrounds, learning styles, and information needs; a hybrid framework is needed to apply the activities and benefits of collaborative knowledge building to an individual's acquisition of knowledge. A system based upon such a framework encourages team members to share knowledge, resources, insights and opinions collaboratively, thus providing a rich experience of discussion, co-discovery and innovation. At the same time, these shared resources and discussions can be filtered to a personal learning space in which each individual team member can further explore and reflect on the resources best suited to his current understanding, experience, cultural background and, most importantly, knowledge needs.